THE PRINCIPLE OF SOCIAL AND CULTURAL MEDIATION FOR DETERMINING THE TYPES OF TEACHERS BY THE STRUCTURE OF SELF-CONTROL AND AGGRESSION INTERRELATIONS - Tatiana Banshikova; Maksim Sokolovsky (Вестник Северо-Кавказского федерального университета)
The article highlights the types of teachers have similarity by similarity ofpersonality dispositions that lead to self-regulation of the aggressive manifestations. The basis for constructing a typology was based on the principle of social and cultural mediation. K-means clustering and analysis of variance have been used as main computation algorithms.